2021
DOI: 10.3390/nu13072259
|View full text |Cite
|
Sign up to set email alerts
|

The Role of BMI, Body Fat Mass and Visceral Fat in Executive Function in Individuals with Overweight and Obesity

Abstract: Evidence accumulated to date suggests that excess weight in the adult population is associated with a wide range of impairments in executive function. However, most studies have only examined the influence of body mass index (BMI) on the cognitive function of individuals with overweight and obesity. This study examined the potential associations of markers of adiposity (BMI, body fat, and visceral fat) with five domains of executive function including cognitive flexibility, inhibition, monitoring, planning, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 33 publications
2
4
0
Order By: Relevance
“…This area acts as a mediator between information from posterior sensory areas and the limbic system, thus integrating and providing feedback between sensory and emotional information with the purpose of organizing behavior to achieve a specific goal ( 37 ). The association between obesity and lower memory performance found in our study is in line with previous studies that have suggested that working memory is frequently affected by higher BMI ( 15 , 23 , 27 ). Some mechanisms may explain these results.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This area acts as a mediator between information from posterior sensory areas and the limbic system, thus integrating and providing feedback between sensory and emotional information with the purpose of organizing behavior to achieve a specific goal ( 37 ). The association between obesity and lower memory performance found in our study is in line with previous studies that have suggested that working memory is frequently affected by higher BMI ( 15 , 23 , 27 ). Some mechanisms may explain these results.…”
Section: Discussionsupporting
confidence: 93%
“…These results might indicate that visceral fat and WHR, apart from increasing the adipose tissue surrounding the intra-abdominal organs ( 58 ), might also have a significant impact on organs, such as the brain. There is consistent evidence that suggests body fat plays a more direct role in the brain, rather than visceral fat and WHR ( 15 , 59 ). This suggests that it is important to study the adiposity continuum and to use complementary measures rather than only BMI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is not readily apparent why self-identifying as Asian or Pacific Islander was associated with membership in the low interpersonal effectiveness class and warrants evaluation in a more ethnically diverse sample [31]. In our study, a higher BMI and lower levels of physical activity were associated with worse performance on the interpersonal effectiveness subscale, consistent with studies reporting that a higher BMI and lower levels of physical activity were associated with worse performance on measures of information processing and executive functions that require inhibitory control and working memory [52][53][54][55]. Our findings suggest that because these two characteristics are associated with interpersonal effectiveness, they may affect cognitive flexibility as well.…”
Section: Demographic and Clinical Characteristicssupporting
confidence: 86%